Unlocking the Potential of Biochar Based Slow-Release Fertilizers: a Systematic Review - Jaini Fakhrudin; Dody Radiansah (International Journal of Sustainability in Research, 2023)
Traditional fertilizer application methods are inefficient and environmentally harmful. Biochar releases nutrients gradually, providing a steady supply to plants while reducing leaching and runoff. Additionally, biochar enhances soil physical properties, such as water retention and structure, leading to improved fertility and plant growth. To fully understand the potential of biochar-based slow-release fertilizers, a systematic review is proposed. The study aims to assess their effectiveness, understand underlying mechanisms, and identify limitations or challenges. It selected studies that investigate biochar-based fertilizers and their effect on the plant growth, nutrient release, and soil fertility. Understanding these production methods is crucial for optimizing the characteristics of biochar-based fertilizers. Overall, this review contributes to the development of sustainable agricultural practices.